2015
DOI: 10.1039/c5sm00427f
|View full text |Cite
|
Sign up to set email alerts
|

Jumping acoustic bubbles on lipid bilayers

Abstract: In the context of sonoporation, we use supported lipid bilayers as a model for biological membranes and investigate the interactions between the bilayer and microbubbles induced by ultrasound. Among the various types of damage caused by bubbles on the surface, our experiments exhibit a singular dynamic interaction process where bubbles are jumping on the bilayer, forming a necklace pattern of alteration on the membrane. This phenomenon was explored with different time and space resolutions and, based on our ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…5,6 Recent studies have reported the shedding of surface material from phospholipid-coated MBs, 7 the deposition of liposomal lipids onto cell membranes, 8 and the transfer of lipids from phospholipid-shelled MBs to synthetic membranes during ultrasound excitation in vitro. 9 Previous work by the authors has also shown that lipid transfer from MBs to cell membranes influences membrane hydration and lipid order. 10 Critically, this effect was found to be highly dependent on the MB formulation (i.e., carrier lipid chain length, emulsifier species, and molar ratio of lipid to emulsifier).…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…5,6 Recent studies have reported the shedding of surface material from phospholipid-coated MBs, 7 the deposition of liposomal lipids onto cell membranes, 8 and the transfer of lipids from phospholipid-shelled MBs to synthetic membranes during ultrasound excitation in vitro. 9 Previous work by the authors has also shown that lipid transfer from MBs to cell membranes influences membrane hydration and lipid order. 10 Critically, this effect was found to be highly dependent on the MB formulation (i.e., carrier lipid chain length, emulsifier species, and molar ratio of lipid to emulsifier).…”
Section: Introductionmentioning
confidence: 92%
“…Exposure to microbubbles (MBs) and ultrasound can induce an increase in cell permeability (sonoporation) offering a promising modality for noninvasively increasing the local uptake of therapeutics in a range of applications, including cancer and neurodegenerative diseases. A range of potential mechanisms have been proposed to explain the process of sonoporation, but this remains an area of active research. , Recent studies have reported the shedding of surface material from phospholipid-coated MBs, the deposition of liposomal lipids onto cell membranes, and the transfer of lipids from phospholipid-shelled MBs to synthetic membranes during ultrasound excitation in vitro . Previous work by the authors has also shown that lipid transfer from MBs to cell membranes influences membrane hydration and lipid order .…”
Section: Introductionmentioning
confidence: 99%